1983
DOI: 10.1346/ccmn.1983.0310201
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fixation by Clay Minerals during Hydrothermal Treatment

Abstract: Abstract--The amount of K fixed in K-and Ca-saturated montmodUonite, vermiculite (trioctahedral), rectorite-type and IMII-ordered mica/montmorillonites was measured as a function of time (1-64 days), temperature (25~176 pH (6.0, 9.7, and 10.7), and K-concentration (0.02 and 1.0 M) in solution. The amount of K fixed by the clays generally increased with increasing temperature, pH, and K-concentration and reached saturation in response to each experimental condition in 5 or 6 days. The K-montmorillonite and K-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 28 publications
(25 reference statements)
2
43
0
Order By: Relevance
“…Many researchers have emphasized that high activities of K in pore fluids or in precursor smectite promote the transition to illite (Eberl and Hower 1976;Roberson and Lahann 1981;Howard and Roy 1985;Inoue 1983;Whitney and Northrop 1988). Huang et al (1993) recently quantified such relations.…”
Section: Relation Of Interlayer Cation Composition To the Smectite-tomentioning
confidence: 99%
“…Many researchers have emphasized that high activities of K in pore fluids or in precursor smectite promote the transition to illite (Eberl and Hower 1976;Roberson and Lahann 1981;Howard and Roy 1985;Inoue 1983;Whitney and Northrop 1988). Huang et al (1993) recently quantified such relations.…”
Section: Relation Of Interlayer Cation Composition To the Smectite-tomentioning
confidence: 99%
“…A more detailed description of the analytical techniques used can be found in Inoue et al (1978) and Inoue (1983); complete data are reported in Inoue et al (1978) and Inoue (1980).…”
Section: Ka-]mentioning
confidence: 99%
“…The kinetics of the smectite to illite reaction during shale diagenesis have been studied extensively using experimental techniques (Eberl and Hower, 1976;Roberson and Lahann, 1981;Inoue, 1983;Howard and Roy, 1983;Whitney and Northrop, 1988;Whitney, 1990). Huang et al (1991) have shown that illite/smectite composition versus depth profiles can be calculated using an experimentally derived kiCopyright 9 1993, The Clay Minerals Society netic model assuming knowledge of pore fluid K concentration.…”
Section: Introductionmentioning
confidence: 99%